Genetics and Sports (Medicine and Sport Science, 54, 2009)
This publication reviews past, current and future applications of genetic research in the fields of exercise science and sports medicine. It highlights ethical concerns, potential clinical applications and exploitation of genetic information. The authors, an interdisciplinary group of experts comprising clinicians, exercise scientists, human geneticists and other biological scientists, present an integrated and holistic understanding of the field to the reader. Several chapters of the book address the issue of nature and nurture in determining athletic ability and etiology of sports injuries. Other chapters are dealing with genetics and performance research during premolecular and molecular biology eras, gene-lifestyle interactions and their consequences on health, as well as genetic risk factors in musculoskeletal soft tissue injuries. Finally, the possible application of gene therapy in athletes, gene doping and genetic testing of athletes are discussed. The book is highly recommended to exercise scientists, sports clinicians, human geneticists, athletes, coaches and to all those interested in the relatively new area of genetic research within the fields of exercise science and sports medicine.